On-chip plasmonic spin-Hall nanograting for simultaneously detecting phase and polarization singularities - Feng, Fu (Light Sci Appl, 2020)
Phase and polarization singularities are important degrees of freedom for electromagnetic field manipulation. Detecting these singularities is essential for modern optics, but it is still a challenge, especially in integrated optical systems. In this paper, we propose an on-chip plasmonic spin-Hall nanograting structure that simultaneously detects both the polarization and phase singularities of the incident cylindrical vortex vector beam (CVVB). The nanograting is symmetry-breaking with different periods for the upper and lower parts, which enables the unidirectional excitation of the surface plasmon polariton depending on the topological charge of the incident optical vortex beam. Additionally, spin-Hall meta-slits are integrated onto the grating so that the structure has a chiral response for polarization detection. We demonstrate theoretically and experimentally that the designed structure fully discriminates both the topological charges and polarization states of the incident beam simultaneously. The proposed structure has great potential in compact integrated photonic circuits.